Peran Kelompok Teror dalam Hubungan Antar Negara-Negara Asia Tenggara - Laila Indriyanti Fitria (Jurnal Alternatif - Jurnal Ilmu Hubungan Internasional, 2023)
Terrorist group has been categorized as one of the actor in international relations. The rise of Uighur terrorist in the 2017 adds a new dimension to the threat from terrorism in Southeast Asia, as argued by Singh (2016) and Soliev (2017). Their existence in Southeast Asia hampers the relations between Southeast Asia countries with China. The Uighurs are minor Muslim ethnic residing in Western part of China which resort to violence and terror since 1992 due to extreme repression from Chinese government. Failure to break government’s oppression, they transforms themselves from local terrorist group to sep up international network. This paper identiefies the spread of Uighur terrorist network from China to Indonesia and their intention of coming to Indonesia. Focusing on the extremist Uighur group, this research identifies the threat that Indonesia’s government facing in the future when these Uighurs came to Indonesia claiming themselves as asylum seeker. Key Word : Uighur; East Turkestan Islamic Movement (ETIM); Political Repression; Southeast Asia Terrorism;